2019
DOI: 10.1002/jbm4.10205
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of FGF Signaling by Spry4 Overexpression Leads to Shape Impairment, Enamel Irregularities, and Delayed Signaling Center Formation in the Mouse Molar

Abstract: FGF signaling plays a critical role in tooth development, and mutations in modulators of this pathway produce a number of striking phenotypes. However, many aspects of the role of the FGF pathway in regulating the morphological features and the mineral quality of the dentition remain unknown. Here, we used transgenic mice overexpressing the FGF negative feedback regulator Sprouty4 under the epithelial keratin 14 promoter (K14‐ Spry4 ) to achieve downregulation of signaling in the epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…As we hypothesized from the previous reports (Gritli‐Linde et al, 2002; Li et al, 2018; Liu et al, 2008; Marangoni et al, 2019; Xiong et al, 2019) and our functional evaluation using an in vitro cultivation, 3 weeks calcified teeth showed the altered morphogenesis with smaller size, fewer cusps and disrupted pattern of enamel and dentin arrangements in OGT inhibited teeth (Figure 5). This altered morphogenesis of teeth would be related with the alterations in functional regulations including Fgf4, Shh, and Wnt signalings (Figure 3).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As we hypothesized from the previous reports (Gritli‐Linde et al, 2002; Li et al, 2018; Liu et al, 2008; Marangoni et al, 2019; Xiong et al, 2019) and our functional evaluation using an in vitro cultivation, 3 weeks calcified teeth showed the altered morphogenesis with smaller size, fewer cusps and disrupted pattern of enamel and dentin arrangements in OGT inhibited teeth (Figure 5). This altered morphogenesis of teeth would be related with the alterations in functional regulations including Fgf4, Shh, and Wnt signalings (Figure 3).…”
Section: Discussionsupporting
confidence: 79%
“…This altered morphogenesis of teeth would be related with the alterations in functional regulations including Fgf4, Shh, and Wnt signalings (Figure 3). Downregulation of Fgf signaling induced enamel irregularities, delayed signaling center formation, and smaller teeth (Marangoni et al, 2019). This was evident in OGT‐inhibited kidney calcified teeth (Figures 3 and 5).…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis showed that BMP4 signaling is critical during the early stages of both the OE to DE and DE to OEE transition, suggesting that loss of BMP4 may lead to agenesis by disrupting these transitions. In other studies, disruption of FGF signaling leads to enamel irregularities (Marangoni et al, 2019). Using AI-based protein design, we now revealed that FGF signaling is essential at the point of ameloblast maturation, suggesting that these irregularities are a result of failure of ameloblasts to mature.…”
Section: Discussionmentioning
confidence: 55%
“…Loss of Spry2 and Spry4 results in persistent expression of FGFs during early tooth development, inducing ectopic molar formation in the normally toothless region called the diastema (Klein et al, 2006). Conversely, epithelial overexpression of Spry4 represses FGF signaling, resulting in delayed development of the mouse molar (Marangoni et al, 2019).…”
Section: The Cap and Bell Stagesmentioning
confidence: 99%